Forest biodiversity monitoring: Guide to community-based approaches - Welter, Z.; Jalonen, R. (Bioversity International, 2019)
Monitoring of natural resources and their management is a key element for effective decision-making in constantly changing and uncertain situations. Monitoring can reduce risks, increase transparency and accountability, enhance learning, and improve the successful implementation of activities. It helps ensure that changes to management approaches come from learning and reflection instead of hasty reactions or unilateral decisions.